KONSUMSI MINUMAN BERKALORI TINGGI SEBAGAI FAKTOR RISIKO TERJADINYA OBESITAS PADA REMAJA SEKOLAH MENENGAH ATAS (SMA) DI KOTA YOGYAKARTA - , YOSI MARATUL AFIFAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : obesity is one of the nutritional problems that occur in Indonesia. Obesity is associated with morbidity and mortality due to impact on the occurrence of degenerative disease such as heart disease, diabetes mellitus and gastrointestinal cancer. Many factors that cause obesity, one of the factors that cause obesity is consumption of sugar sweetened beverages wich containing high calories but low nutrients. Puropose : this research aimed to investigate risk factor for consumption of sugar sweetened beverages on the incidence of obesity in high school students in Yogyakarta. Methode : this research is an observational study using case-control design. The samples in this research are 170 students consisting of 85 obese high school adolescent and 85 non-obese high school adolescent. Measurement of obesity status was taken by measurement of weight and height based on the reference standard of WHO. Data of consumption sugar sweetened beverages is collected by using SQFFQ. Data were analyzed by Mann-whitney test and Chi square test. Result : the relationship between consumption of sugar sweetened beverages and obesity is not statistically significant (p > 0,05). Conclusion : consumption of sugar sweetened beverages doesnât become a risk factor of obesity among student high school in Yogyakarta. Keyword : sugar sweetened beverages, adolescent, obesity.